S,O-Ligand-Promoted Palladium-Catalyzed C–H Functionalization Reactions of Nondirected Arenes - Naksomboon, Kananat (ACS Catal, 2017)
[Image: see text] Pd(II)-catalyzed C–H functionalization of nondirected arenes has been realized using an inexpensive and easily accessible type of bidentate S,O-ligand. The catalytic system shows high efficiency in the C–H olefination reaction of electron-rich and electron-poor arenes. This methodology is operationally simple, scalable, and can be used in late-stage functionalization of complex molecules. The broad applicability of this catalyst has been showcased in other transformations such as Pd(II)-catalyzed C–H acetoxylation and allylation reactions.